COMPARISON OF THE EFFECT OF PHYSIOTHERAPY ON INCREMENTAL SHUTTLE WALK DISTANCE IN LOBECTOMY PATIENTS WITH VATS AND THORACOTOMY - Kritsnakriengkrai, Sukalya; Vaewthong, Napaporn; Donkaew, Oraphan; Chimpalee, Jaturong; klungthumnium, Jirawat; Kaweemaythee, Thanthai; Sriphol, Pharadorn; Songtanin, Vachiravit; Horbut, Voradorn; Thusombat, Yachuravej (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The evidence studies of the effect of physiotherapy on incremental shuttle walk distance in lobectomy patients are limited. The purposes of this study were to examine the effect of physiotherapy on the change in shuttle walk distance after lobectomy and to compare shuttle walk distance between lobectomy with video-assisted thoracoscopic surgery (VATS) and lobectomy with Thoracotomy groups. This retrospective study included patients who underwent lobectomy via VATS or Thoracotomy and received physical therapy treatment including breathing training, cough training, and exercise, between April 2015 and December 2020 at the Central Chest Institute of Thailand. The incremental shuttle walk test (ISWT) was investigated at preoperative, postoperative discharge day, and at 2 weeks follow-up. The data of shuttle walk distances between VATS and Thoracotomy groups in each time period were analyzed using Two-way Mixed ANOVA. The results showed that there were 190 eligible patients who underwent lobectomy via VATS (n=125) or Thoracotomy (n=65) and received physical therapy treatment. The shuttle walk distances were significantly decreased at discharge day when compared to preoperative values (p<0.001) and were returned to the preoperative level at 2 weeks follow-up. When comparing between VATS and Thoracotomy groups on discharge day, the shuttle walk distance in VATS was decreased less than in Thoracotomy groups, and both groups recovered within 2 weeks of follow-up. The conclusion was that patients undergoing lobectomy via VATS or Thoracotomy and receiving physical therapy treatment had a significant postoperative reduction of shuttle walk distance, however, they recovered to the preoperative levels within 2 weeks of follow-up.